Embodiment and dementia: Exploring critical narratives of selfhood, surveillance, and dementia care. (May 2013) - Kontos, Pia; Martin, Wendy
In the last decade there has been a notable increase in efforts to expand understandings of dementia by incorporating the body and theorizing its interrelationship with the larger social order. This emerging subfield of dementia studies puts the body and embodied practices at the center of explorations of how dementia is represented and/or experienced. This shift towards a greater recognition of the way that humans are embodied has expanded the horizon of dementia studies, providing the intellectual and narrative resources to examine experiences of dementia, and their interconnections with history, culture, power, and discourse. Our aim in this paper is to critically explore and review dimensions of this expanding research and literature, specifically in relation to three key narratives: (1) rethinking selfhood: exploring embodied dimensions; (2) surveillance, discipline, and the body in dementia and dementia care; and (3) embodied innovations in dementia care practice. We argue that this literature collectively destabilizes dementia as a taken-for-granted category and has generated critical texts on the interrelationship between the body and social and political processes in the production and expression of dementia.